Implementation of Shokyakuro-FTU Incinerator to process residual waste towards Unisba's zero-waste campus - Prasetyaningsih, Endang; Najamudin, Yan Orgianus; Satori, Mohamad; Oemar, Hirawati; Susilo, Putri Aulia (Universitas Lancang Kuning, 2024)
Unisba's waste problem was solved by establishing a compost hut to sort organic, recyclable, and residual waste, which the Clean and Green Team managed. Organic waste is composted; recyclable waste is separated, cleaned, and sold to Bandung City's main waste bank; and residual waste is transported by the Cleaning Technical Unit (UPTD) Bandung City. Unisba has launched a long-term initiative to become a zero-waste campus by managing waste independently. As part of this program, the Shokyakuro -FTU Incinerator machine will process residual waste on Campus 2 Unisba Ciburial and replace the processing of residual waste by UPTD. This service activity aims to use the Shokyakuro -FTU Incinerator machine to process residual waste at Campus 2 Unisba in Ciburial District, Bandung Regency. All cleaning staff practice in Campus 2 Unisba Ciburial operating the Shokyakuro -FTU Incinerator machine as part of the implementation process. Following training, machine operating procedures are developed to make it easier for cleaning staff to use the machine in the future.